TRANSFORMASI KURIKULUM PESANTREN: Telaah Pemikiran KH. MA. Sahal Mahfudh dan Nurcholish Madjid - Mukhlison Effendi; Suradi Suradi (Cendekia: Kependidikan dan Kemasyarakatan, 2014)
Abstract; Islamic boarding school is an indigenous Indonesia. Some contribution that given in the Islamization process, create a good community literacy and culture are very large. One reason, because there are Islamic boarding school curriculum transformation. Most influential enticement are KH. MA. Sahal Mahfudh and Nurcholish Madjid enticement. To knowing and determine the transformation both of those figures, the researcher take focus of study as: 1) the speculation of KH. MA. Sahal Mahfudh about islamic boarding school curriculum transformation. 2) The speculation of Nurcholish Madjid about islamic boarding school curriculum transformation. 3) The equation and differences between KH. MA. Sahal Mahfudh and Nurcholish Madjid speculation about Islamic boarding school curriculum transformation.Based on the focus of the study above, the researcher tries to answer through some research with use descriptive approach and library research types, while the data collection that used in this research is literary techniques. The data analysis that used in this research consisted of content analysis and comparative analysis.The conclusion of this study are both of KH. MA. Sahal Mahfudh and Nurcholish Madjid made an offer about Islamic boarding school curriculum transformation. The equation of their speculation about Islamic boarding school curriculum transformation occur in all of component of curriculum. The differences both of their speculation site in how to formulate Islamic boarding school curriculum transformation. KH. MA. Sahal Mahfudh take a more specific formulation in this transformation, whereas Nurcholish Madjid make a global transformation. Moreover, caused of the different interpretation of the motto al-muha>faz}otu ‘ala al-qodimi al-solih wa al-akhdu bi al-jadidi al-aslahu. ملخص: البسنترينات هي المؤسسة التعليمية الأصيلة لدى إندونيسيا. ولها اسهامات كبيرة في إسلامية المجتمع الإندونيسي المثقف. وهذا بتغيّر المنهج في البسنترينات. وفي هذا الصدد تظهر أهمية فكرة كياهي الحاج سهل محفوظ ونور خالص مجيد. ولمعرفة فكرتهما أكثرعن هذا فالباحث يركز بحثه في : 1) فكرة كياهي الحاج سهل محفوظ عن تغيّر المنهج الدراسي في البسنترينات، 2) فكرة نور خالص مجيد عن تغيّر المنهج الدراسي في البسنترينات، والفرق بينهما وأوجه التشابه  بينهما في هذه المسألة. انطلاقا من موضوع البحث السابق، فحاول الباحث إجابة الأسئلة عن طريق البحث بالمدخل الوصفي ونوعه الدراسة المكتبية. استخدم الباحث لجمع بيانات البحث أسلوب الوثائق المكتوبة، وكان التحليل تحليل المضمون والتحليل المقارن. ونتيجة البحث إنهما ( سهل محفوظ ونور خالص مجيد) اقترحا طراز تغيير المنهج الدراسي في البسنترينات. وأما أوجه التشابه بين فكرتهما تكون في جميع عناصر المنهج. والفرق بين فكرتهما يكون في كيفية تكوين هذا التغيير في المنهج الدراسي. اتخذ سهل محفوظ التكوين الخاص في هذا الأمر وأما نور خالص مجيد فاتخذ طراز التكوين العام. وهذا نتيجة وجود الاختلاف في فهم وتفسير القاعدة " المحافظة على القديم الصالح والأخذ بالجديد الأصلح " . Keyword: Curriculum transformation, islamic boarding school, pesantren.